What influences the purchase intention of online travel consumers? - Tam, Carlos (2022)
Tam, C., Pereira, F. C., & Oliveira, T. (2024). What influences the purchase intention of online travel consumers? Tourism and Hospitality Research, 24(2), 304-320. https://doi.org/10.1177/14673584221126468 --- Funding: This work was supported by national funds through FCT (Fundação para a Ciência e a Tecnologia), under the project - UIDB/04152/2020 - Centro de Investigação em Gestão de Informação (MagIC)/NOVA IMS.